2021
DOI: 10.3390/cancers13112845
|View full text |Cite
|
Sign up to set email alerts
|

RAD51D Aberrant Splicing in Breast Cancer: Identification of Splicing Regulatory Elements and Minigene-Based Evaluation of 53 DNA Variants

Abstract: RAD51D loss-of-function variants increase lifetime risk of breast and ovarian cancer. Splicing disruption is a frequent pathogenic mechanism associated with variants in susceptibility genes. Herein, we have assessed the splicing and clinical impact of splice-site and exonic splicing enhancer (ESE) variants identified through the study of ~113,000 women of the BRIDGES cohort. A RAD51D minigene with exons 2–9 was constructed in splicing vector pSAD. Eleven BRIDGES splice-site variants (selected by MaxEntScan) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 72 publications
(99 reference statements)
1
21
0
2
Order By: Relevance
“…Dominant negative mutations in RAD51 protein variants are suggested to be associated with the Fanconi anemia subtype [51]. Pre-mRNAs of different members of RAD51 are subjected to alternative splicing and are believed to have impacts on cancer progression [52][53][54]. Our results correspond to the inability of truncated RAD51A splice variants to promote homological recombination and reduce DNA damage because Put induced the predominance of the FL variant and prevented the death of normal CD4 + T cells.…”
Section: Discussionmentioning
confidence: 58%
“…Dominant negative mutations in RAD51 protein variants are suggested to be associated with the Fanconi anemia subtype [51]. Pre-mRNAs of different members of RAD51 are subjected to alternative splicing and are believed to have impacts on cancer progression [52][53][54]. Our results correspond to the inability of truncated RAD51A splice variants to promote homological recombination and reduce DNA damage because Put induced the predominance of the FL variant and prevented the death of normal CD4 + T cells.…”
Section: Discussionmentioning
confidence: 58%
“…As already justified in previous studies by our group [ 19 , 20 , 25 ], once experimental splicing data were available, splicing predictive codes PVS1 and PP3 did not contribute to our final classification. Similarly, in HBOPC_ATMv1 specifications, functional splicing codes replace rather than combine with predictive splicing codes.…”
Section: Methodsmentioning
confidence: 69%
“…MCF-7 and MDA-MB-231 cell culture, transfection, and inhibition of the nonsense-mediated decay were performed as previously described [ 19 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Functional assays of VUS provide critical information for their clinical interpretation. Aberrant splicing is a known frequent mechanism of gene inactivation associated with germline variants in BC genes [20,21,24,39]. Herein, we have focused on 82 PALB2 variants located at the splice-site boundaries detected in the BRIDGES cohort, so that we have accomplished the largest splicing functional study of PALB2 by minigenes to date.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that spliceogenic variants make a significant contribution to the overall pool of germ‐line loss of function alleles in the BC/OC genes RAD51C [ 20 ], RAD51D [ 21 ], and BRCA2 [ 22 , 23 , 24 ]. The present work was carried out in the context of the Breast Cancer After Diagnostic Gene Sequencing (BRIDGES) project ( https://bridges-research.eu/ ), where 34 known or suspected BC/OC genes were sequenced in 60,466 BC cases and 53,461 controls [ 8 ].…”
Section: Introductionmentioning
confidence: 99%